Relationships between temperament, character, motivation for games and problematic video game-play among adolescents in Ahwaz, Iran - Mohammadzadeh, Parvin (2016)
The progression of electronic and video games can be a serious threat for children and adolescents and put them at higher risk of addictive behaviour. The aim of this study is examining the moderating effect of gender on temperament, character, motivation of game, and Problematic video game play among adolescents in Ahwaz, Iran. A total of 400 adolescents from four boys and eight girls’ high schools in eight regions of Ahwaz were selected using multistage stratified sampling. Data was collected using a self-administered questionnaire, which included a Problematic Video Game Test (PVGT), Temperament-Character Inventory (TCI), and Problematic video game play Motivation Scales (VGMS). Descriptive statistics were used to describe adolescents’ characteristics such as gender and academic levels, motivation of games (intrinsic motivation, extrinsic motivation, and amotivation), temperament (novelty seeking, harm avoidance, reward dependence, and persistence), character (self-directedness, self-transcendences, and cooperativeness), and Problematic video game play. Hierarchical regression analyses and post-hoc regression analysis were used to determine the moderating effect. Based on the result, the findings highlighted that gender could moderate the relationships between intrinsic motivation to know (b=2.32, t=16.148, p˂.001), intrinsic motivation experience, stimulation (b=2.34, t=16.758, p˂.001) with Problematic video game play, and additionally, extrinsic motivation identified (b=2.77, t=19.571, p˂.001), extrinsic motivation introjected (b=2.51, t=16.279, p˂.001), extrinsic motivation external regulation (b=2.36, t=14.566,p˂.001), and amotivation (b=2.17, t=13.475, p˂.001) with Problematic video game play. In conclusion, the gender variable could have an impact on six types of motivation associated with games and Problematic video game play, although gender does not have an impact on intrinsic motivation to accomplish. Therefore, the results emphasized gender roles as having moderating effects on the relationships between intrinsic motivation, extrinsic motivation, and amotivation with Problematic video game play. In contrast, the results showed that gender did not moderate the relationship between seven dimensions of temperament and character with Problematic video game play, the variable had equal effects on both males and females. In conclusion, although some dimensions of temperament and character correlated with Problematic video game play but motivation of games is main response driver of technology use such as Problematic video game play. Moreover, by using the moderating effects of gender, the interaction is significant for females who had high intrinsic motivation to know, to experience stimulation, extrinsic motivation to introjected, identified, external regulation and amotivation. The study presents more information about predictive factors of Problematic video game play through focusing on temperament, character, motivation of games, and gender as predictive factors. It shed some light on the impact of gender on Problematic video game play.